Accuracy of a Smartphone-based Autorefractor Compared with Criterion-standard Refraction. Issue 12 (December 2018) - Jeganathan, V. Swetha E.; Valikodath, Nita; Niziol, Leslie M.; Hansen, Sean; Apostolou, Hannah; Woodward, Maria A.
Abstract : SIGNIFICANCE: Uncorrected refractive error is a prevalent problem throughout the world especially among the low-income population who have limited access to professional eye care and cannot afford eyeglasses. PURPOSE: The purpose of this study was to evaluate the accuracy and usability of a low-cost, portable, smartphone-based autorefractor (Netra, EyeNetra Inc., Somerville, MA) in adults. METHODS: A cross-sectional study was conducted to compare the portable refractor with subjective (manifest and cycloplegic) refraction for sequential adult participants with best-corrected visual acuity of 20/40 or greater. For each method of refraction, the spherical equivalent was calculated. Differences between methods were tested with linear mixed regression models. A validated usability questionnaire was administered regarding ease of use (100-point scale, higher scores better) for the portable autorefractor. RESULTS: Eighty-seven subjects (152 eyes) were studied (age range, 20 to 90 years; mean ± standard deviation, 51.9 ± 18.3 years). Mean spherical equivalent by the portable device was −2.76 D (range, −14.75 to 3.63 D) compared with −2.49 D (range, −15.25 to 4.25 D) by manifest refraction. The mean relative difference in spherical equivalent between methods was −0.27 D ( P = .001, significantly different than 0 D). The mean absolute difference between methods was 0.69 D ( P < .001, significantly different than 0.5-D absolute difference). Similar results were found when comparing spherical equivalent between Netra and cycloplegic refraction methods. Subjects reported average ease of use for the Netra of 75.4 ± 19.8. CONCLUSIONS: The portable autorefractor had small but clinically significant differences from subjective refraction. The device's scores on the usability scale indicate good overall patient acceptance. The device may be valuable for use where there is limited access to a trained refractionist. Abstract : Supplemental digital content is available in the text.